Clearing the tracks of the White Pass & Yukon Railroad after a snow storm on the summit of White Pass, Alaska, March 20, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Clearing the track after a snow storm on the summit of White Pass and Yukon Route. Mar 20 '99" Original image in Hegg Album 2, page 28. Klondike Gold Rush.